2020
DOI: 10.1044/2020_aja-19-00125
|View full text |Cite
|
Sign up to set email alerts
|

Auditory Brainstem Response Test at Different Stimulus Rates in Normal-Hearing Adults Living With HIV

Abstract: Purpose The study investigated whether the auditory brainstem response (ABR) at a baseline and at higher repetition rates can detect if neurodegeneration has occurred in adults living with HIV who present with normal behavioral pure-tone thresholds. Method An exploratory research design was used. Forty adults with HIV (80 ears, 57.5% female; M age = 26.3 years, SD = 3.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…An ABR wave I amplitude difference, while not as robust as DPOAE differences, was seen between the groups. Studies have found prolonged peak and interpeak latencies, but to our knowledge, no other study has reported a difference in ABR wave I amplitude between young PLWH and HIV‐negative controls 10,17–19 . As ABR wave I represents the distal function of the auditory nerve at the spiral ganglion cells, we might interpret this as a slight reduction in neural strength from the hair cell to the cochlear nucleus in PLWH 19 , 20 .…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…An ABR wave I amplitude difference, while not as robust as DPOAE differences, was seen between the groups. Studies have found prolonged peak and interpeak latencies, but to our knowledge, no other study has reported a difference in ABR wave I amplitude between young PLWH and HIV‐negative controls 10,17–19 . As ABR wave I represents the distal function of the auditory nerve at the spiral ganglion cells, we might interpret this as a slight reduction in neural strength from the hair cell to the cochlear nucleus in PLWH 19 , 20 .…”
Section: Discussionmentioning
confidence: 85%
“…Studies have found prolonged peak and interpeak latencies, but to our knowledge, no other study has reported a difference in ABR wave I amplitude between young PLWH and HIV-negative controls. 10,[17][18][19] As ABR wave I represents the distal function of the auditory nerve at the spiral ganglion cells, we might interpret this as a slight reduction in neural strength from the hair cell to the cochlear nucleus in PLWH. 19,20 Potential cochlear synaptic dysfunction may not be apparent in peripheral auditory measures such as pure tone audiometry, perhaps explaining why audiometric thresholds were similar between groups.…”
Section: Discussionmentioning
confidence: 99%
“…Virus-related hearing losses are mostly sensorineural, although they can also be of the conductive or mixed type. Such virus-related hearing losses can occur unilaterally or bilaterally, and can be reversible or irreversible [8] , [9] . The most common viral etiology of hearing loss is the measles virus causing otosclerosis.…”
Section: Introductionmentioning
confidence: 99%